1985
DOI: 10.1159/000265363
|View full text |Cite
|
Sign up to set email alerts
|

Light and Electron Microscopic Studies of the Rat Hyalocyte after Perfusion Fixation

Abstract: The characteristic morphology of a not intentionally stimulated hyalocyte is described, using TEM and perfusion fixation. The best results were obtained by retrograde perfusion via the abdominal aorta with a glutaraldehyde- and formaldehyde-containing fixative. The cells, situated in the cortical area of the vitreous body, show mostly an indented nucleus, primary and secondary lysosomes, mitochondria, cisterna, clusters of free ribosomes and a Golgi apparatus. Bristle-coated micropinocytotic vesicles can also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…These cells organize into the proliferative membrane (3,4). Hyalocytes are found in the cortical vitreous in the vicinity of the inner retinal surface (5). Morphological studies suggest that hyalocytes may belong to the monocyte/ macrophage lineage (6,7).…”
mentioning
confidence: 99%
“…These cells organize into the proliferative membrane (3,4). Hyalocytes are found in the cortical vitreous in the vicinity of the inner retinal surface (5). Morphological studies suggest that hyalocytes may belong to the monocyte/ macrophage lineage (6,7).…”
mentioning
confidence: 99%
“…Hyalocytes are the cells located in the cortical vitreous abutting the inner surface of the retina (21). Morphological studies have demonstrated that hyalocytes, which possess lysosome-like granules, mitochondria, and micropinocytotic vesicles in their cytoplasm, belong to the monocyte/ macrophage lineage (22)(23)(24).…”
mentioning
confidence: 99%
“…2 It is reported that the hyalocytes mainly subsist in the vitreous cortex, vitreous base, and posterior chamber. 3,4 Histologically, the hyalocytes have characteristics similar to those of macrophages. They possess lysosomes, mitochondria, ribosomes, and micropinocytotic vesicles, 3 and express leukocyte-associated antigens CD45, CD11a, CD64, and S-100 and major histocompatibility complex class I and II, but do not express CD68, CD11b, CD14, glial fibrillary acidic protein (GFAP), and cytokeratin.…”
mentioning
confidence: 99%
“…3,4 Histologically, the hyalocytes have characteristics similar to those of macrophages. They possess lysosomes, mitochondria, ribosomes, and micropinocytotic vesicles, 3 and express leukocyte-associated antigens CD45, CD11a, CD64, and S-100 and major histocompatibility complex class I and II, but do not express CD68, CD11b, CD14, glial fibrillary acidic protein (GFAP), and cytokeratin. 5 Although most of the facilities and roles of hyalocytes remain unclear, the hyalocytes are thought to be one of the macrophage lineage and are likely to be broadly associated with physiological and pathologic conditions, including the maintenance of the vitreous as avascular and transparent tissue.…”
mentioning
confidence: 99%